Gelingende digitale Schulentwicklung in der Post-Pandemiezeit - Eickelmann, Birgit (SchulVerwaltung Spezial)

Gelingende digitale Schulentwicklung in der Post-Pandemiezeit - Eickelmann, Birgit (SchulVerwaltung Spezial 2021)

Schule in der digitalen Welt - Buhl, Heike M.; Bonanati, Sabrina; Eickelmann, Birgit

Data Literacy: Kompetenzrahmen für Hochschulen - Bush, Annika; de Gruisbourne, Birte; Matzner, Tobias; Schulz, Christian

Digitale Transformation aus der Perspektive von Kindern und Jugendlichen in Europa gestalten – das Horizon-Projekt DigiGen. PlanBD #4 Around the World - Eickelmann, Birgit; Drossel, Kerstin; Casamassima, Gianna; Labusch, Amelie (Fachmagazin für Schule in der digitalen Welt)

The younger generation’s views on how their education is preparing them for the digital age against the background of COVID-19 - Eickelmann, Birgit; Barbovschi, Monica; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, Greta Björk; Holmarsdottir, Halla Bjork; Kazani, Aggeliki; Mifsud, Louise; Parsanoglou, Dimitris; Port, Sonja; Sisask, Merike; Symeonaki, Maria; et al.

Digital diversity across Europe. Policy brief September 2021 of Working Package 2 'Mapping digital transformations across Europe' in Horizon-2020-Project DigiGen - Ayllón, Sara; Casamassima, Gianna; Drossel, Kerstin; Eickelmann, Birgit; Hyggen, Christer; Lado, Samuel; Port, Sonja; Broekstra, Nienke

„Zunge: Sprache“ Literarische Mehrsprachigkeit im Deutschunterricht am Beispiel der Erzählung „Mutterzunge“ von Emine Sevgi Özdamar - Büttner, Denise; Roll , Heike (Vermitteln - verbinden - verstehen. 46. Jahrestagung des Fachverbandes Deutsch als Fremd- und Zweitsprache an der Technischen Universität Chemnitz)

Consultation Phases in Mathematics Learning and Support Centres - Schürmann, Mirko; Panse, Anja; Shaikh, Zain; Biehler, Rolf; Schaper, Niclas; Liebendörfer, Michael; Hilgert, Joachim (International Journal of Research in Undergraduate Mathematics Education)
Abstract Mathematics Learning Support Centres are becoming more and more common in higher education both internationally and in Germany. Whereas it is clear that their quality largely depends on a functioning interaction in consultations, little is known about how such consultations proceed in detail. On the basis of models from the literature and recorded support sessions (N = 36), we constructed a process model that divides consultations into four ideal–typical phases. In the individual consultations, forward or backward leaps occur, but overall the model seems to describe the data well. A high intercoder reliability shows that it can be applied consistently on real data by different researchers. An analysis of the consultations between students and tutors shows that both mainly work on past attempts or thoughts of the students to solve the exercise or problems and on concrete strategies to solve a problem within the session. In contrast, very little time is dedicated to summarizing and reflecting the solution. The data allows for a more in-depth discussion of what constitutes quality in advising processes and how it might be further explored. Practically, the model may structure support sessions and help in focussing on different goals in different phases.
Keywords: Education; Mathematics (miscellaneous)

Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr